Prevalence and pregnancy outcomes in patients with antepartum haemorrhage in a tertiary hospital in Ibadan, Nigeria - Onebunne, Chinedum A. C.; Aimakhu, Christopher O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Antepartum haemorrhage (APH) as one of the major obstetric emergencies contributing greatly to maternal and fetal morbidity and mortality is of serious concern in the developing world. A retrospective analysis of the APH cases and evaluation of its impact on fetal and maternal outcomes was conducted. Methods: A retrospective study of cases managed between January 2013 and December 2014 at the University College Hospital Ibadan; all cases at a minimum of 28 weeks of gestation with antepartum bleeding were selected. Data was retrieved from the hospital records. Results: Around 5.8% prevalence rate of APH was documented during the study period with placental abruption and placenta praevia accounting for 46.8% and 39.2% of these cases respectively. Only 28.5% of cases were booked. Three-fifths of the women had anemia, 17.7% suffered hypovolemic shock, 33.9% also had primary PPH while 4 out of every 10 (39.8%) were transfused with blood. Seven out of every ten premature deliveries (prior to 34weeks gestation) were due to placental abruption with p value of <0.001. There were 2 maternal deaths (1%), 61 (31%) still births and 11 (5.6%) early neonatal deaths giving a perinatal mortality rate of 35.6%. Conclusions: Antepartum hemorrhage was associated with poor maternal and neonatal outcome in this study. There is need to improve on infrastructures, such as functional blood banks, appropriate antenatal care and referral system in our health facilities to be able to cope with increasing challenges of this obstetric hemorrhage.